Osteoid Osteoma: Can Impedance Levels in Radiofrequency Thermocoagulation Predict Recurrence? - Matthew Ockendon; Jonathan J. Gregory; Gillian L. Cribb; W. Paul Cool; D. Charles Mangham; Radhesh Lalam (Radiology Research and Practice)
Objective. To evaluate rise in impedance during percutaneous radiofrequency thermocoagulation (PRFTC) of osteoid osteomas as a predictor of local recurrence. Design and Patients. A prospective study of 23 patients (24 PRFTC procedures) with minimum of 2.25-year followup (average 3.3 years). Average age 19.6 years (range 4–44), sex ratio 15 : 8 (male : female), 16 nondiaphyseal, 7 diaphyseal. Results. In 19 procedures, an increase in impedance was measured—no recurrences have occurred in this group to date. In 5 procedures, no increase in impedance was seen (3 non-diaphyseal, 2 diaphyseal), and 1 recurrence has been seen in this group to date. This difference is statistically significant with a P value of .05.